2021
DOI: 10.30880/ijie.2021.13.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Multi-objective Optimization of Turning Performance Characteristics using GA Coupled with AHP based Approach

Abstract: Heat resistive super alloys (HRSAs) which are commonly known as Inconel alloys are extensively used in aeronautical, food processing and automobile industries. The machinability and parametric optimization of Inconel 825 have not been reported much in the literatures. This study attempts to experimentally investigate and optimize the process parameters during machining Inconel 825 for multiple performance characteristics. Spindle speed (N), feed rate (f) and depth of cut (d) are optimized for different respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Therefore, the modification of the geometrical and kinematical relations in already existing procedures can lead to good results with small alterations [13]. In traditional turning, better surface roughness can be obtained at high cutting speed and lower feed rate [14]. However, by increasing the inclination angle and choosing a proper cutting tool, the surface quality can be improved even in higher feed rates [15], while the tool life and the friction coefficient between the tool and workpiece will be also better [16].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the modification of the geometrical and kinematical relations in already existing procedures can lead to good results with small alterations [13]. In traditional turning, better surface roughness can be obtained at high cutting speed and lower feed rate [14]. However, by increasing the inclination angle and choosing a proper cutting tool, the surface quality can be improved even in higher feed rates [15], while the tool life and the friction coefficient between the tool and workpiece will be also better [16].…”
Section: Introductionmentioning
confidence: 99%
“…In this study a design of experiment method is applied, which is commonly used in the practice [17]. Tamang et al also applied an experimental design method to optimise the analysed parameters individually, from which one was the Arithmetic Mean Height of the roughness profile [18]. Buj-Corral et al applied 2 5−1 factorial design in their study to analyse the honing process and they found that the main factor affecting roughness was grain size in both cases, followed by pressure [19].…”
Section: Introductionmentioning
confidence: 99%
“…Despite all advantages that turn-milling offers, turn-milling process monitoring is essential for preventing from development self-excited vibration known as chatter vibration, which can arise during machining at any time [12], [13]. The chatter becomes a common limitation to productivity and part quality, accelerates tool wear, and damages the machine-tools shaft [14], [15].…”
Section: Introductionmentioning
confidence: 99%